2010
DOI: 10.1371/journal.pone.0009644
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Promotes Glycogen Accumulation through Hypoxia Inducible Factor (HIF)-Mediated Induction of Glycogen Synthase 1

Abstract: When oxygen becomes limiting, cells reduce mitochondrial respiration and increase ATP production through anaerobic fermentation of glucose. The Hypoxia Inducible Factors (HIFs) play a key role in this metabolic shift by regulating the transcription of key enzymes of glucose metabolism. Here we show that oxygen regulates the expression of the muscle glycogen synthase (GYS1). Hypoxic GYS1 induction requires HIF activity and a Hypoxia Response Element within its promoter. GYS1 gene induction correlated with a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
179
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(204 citation statements)
references
References 37 publications
21
179
2
2
Order By: Relevance
“…In contrast to what has been reported on muscle and hepatic cell lines, 35 total GS levels in neurons remain unchanged in hypoxia, but the enzyme is activated (dephosphorylated). In hypoxia, neuronal glycogen turnover is strongly enhanced by the simultaneous activation of GS and GP (shown in Figure 4G).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to what has been reported on muscle and hepatic cell lines, 35 total GS levels in neurons remain unchanged in hypoxia, but the enzyme is activated (dephosphorylated). In hypoxia, neuronal glycogen turnover is strongly enhanced by the simultaneous activation of GS and GP (shown in Figure 4G).…”
Section: Discussioncontrasting
confidence: 99%
“…Surprisingly, although glycogen was degraded in neurons exposed to hypoxia, the activation state of GS dramatically increased ( Figure 4A 35 total GS activity (a readout of the total amount of protein) remained unaltered ( Figure 4A, right panel). Glycogen synthase showed increased electrophoretic mobility by WB analysis ( Figure 4B, quantification of the WB can be found in Supplementary Figure S3), which is characteristic of the activated, dephosphorylated form of the enzyme.…”
Section: Hypoxia Induces Muscle Glycogen Synthase Activation and Glycmentioning
confidence: 99%
“…Thus, preconditioning, as well as its association with postconditioning prevented the depletion of glycogen storage caused by ischemic process. These results are similar to those of Weiss et al 22 and Pescador et al 23 . The exact molecular mechanism to explain this phenomenon is yet to be understood.…”
Section: Ischemic Pre and Postconditioning In Skeletal Muscle Injury supporting
confidence: 92%
“…A better comprehension of this process could explain physiologic adaptations to hypoxia, and also help to develop therapeutic strategies against diseases which hypoxia plays a major role 23 .…”
Section: Ischemic Pre and Postconditioning In Skeletal Muscle Injury mentioning
confidence: 99%
“…Several studies have considered the mechanism of facilitated glycogen accumulation of OCCC (12,13), but a conclusion has not yet been reached. Some studies have found that the glycogen accumulation in several kinds of tumor cells was accelerated under hypoxic conditions (14)(15)(16)(17)(18). Under such a hypoxic environment, hypoxia-inducible factor 1 (HIF1) is expressed and functions as the main factor regulating the metabolism of the cell (19).…”
Section: Introductionmentioning
confidence: 99%